207k views
1 vote
Simplify (x − 4)(x2 − 2x − 3).

1 Answer

1 vote

How to get answer by Mimiwhatsup:


Distribute\:parentheses\\=xx^2+x\left(-2x\right)+x\left(-3\right)+\left(-4\right)x^2+\left(-4\right)\left(-2x\right)+\left(-4\right)\left(-3\right)\\\mathrm{Apply\:minus-plus\:rules}\\+\left(-a\right)=-a,\:\:\left(-a\right)\left(-b\right)=ab\\=x^2x-2xx-3x-4x^2+4\cdot \:2x+4\cdot \:3\\\mathrm{Apply\:exponent\:rule}:\quad \:a^b\cdot \:a^c=a^(b+c)\\x^2x=\:x^(2+1)=\:x^3\\=x^3\\2xx\\\mathrm{Apply\:exponent\:rule}:\quad \:a^b\cdot \:a^c=a^(b+c)\\xx=\:x^(1+1)=\:x^2\\=2x^2\\4\cdot \:2x\\\\=8x\\


4\cdot \:3\\\mathrm{Multiply\:the\:numbers:}\:4\cdot \:3=12\\Group\:like\:terms\\=x^3-2x^2-4x^2-3x+8x+12\\\mathrm{Add\:similar\:elements:}\:-3x+8x=5x\\=x^3-2x^2-4x^2+5x+12\\\mathrm{Add\:similar\:elements:}\:-2x^2-4x^2=-6x^2\\=x^3-6x^2+5x+12\\Answer: =x^3-6x^2+5x+12

User Ali Abid
by
5.5k points